L' évolution de l’expertise médicale des guérisons de Lourdes au regard de la « conversation de gestes ». Introduction : de quoi rient les rationalistes ? - Ogorzelec, Laetitia (Archives de sciences sociales des religions, 2014)
More than the static confrontation between rationalist and catholic doctors, this article suggests returning on the "conversation" (in the pragmatic sense of the term) established, at the end of the 19th century, between the doctors of the Medical Office of the sanctuary of Lourdes, asked to evaluate the so called "supernatural" remissions, and their detractors: positivists, atheistic doctors or free thinkers... Following the adjustments which they set in the medical phase of the procedure of recognizing Lourdes miracles, we show that the doctors of the sanctuary try hard to remain "truthful" following the medical discourse of the time to keep on setting, at the end of their inquiries, the certainties which the Church expects from them.